The oracle code - Nijkamp, Marieke (DC Comics, 2020)
After a gunshot leaves her paralyzed, Barbara Gordon enters the Arkham Center for Independence, where Gotham's teens undergo physical and mental rehabilitation. Now using a wheelchair, Barbara must adapt to a new normal, but she feels like something is dangerously amiss. When patients go missing, it's up to Barbara to find a way to solve the mystery.